2011
DOI: 10.1007/s00417-011-1761-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab treatment for neovascular glaucoma: histopathological analysis of trabeculectomy specimens

Abstract: The biological effects on angle neovascularization after IVB may involve reduced vascular permeability, decreased inflammatory reaction, loss of vascular function, and endothelial cell degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Intravitreal bevacizumab (IVB) was reported to decrease the concentration of VEGF in the aqueous humor [7], the neovascularization of the anterior chamber, and the IOP to acceptable levels in NVG patients [8-12]. Fluorescein angiography and histochemical investigations demonstrated that there was less vascular permeability and inflammatory reaction in trabecular tissue with IVB than without IVB [13,14]. Another histopathological investigation indicated that IVB may induce changes in immature, newly formed vessels, leading to endothelial apoptosis with vascular regression and inducing the normalization of premature vessels in PDR or NVG eyes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal bevacizumab (IVB) was reported to decrease the concentration of VEGF in the aqueous humor [7], the neovascularization of the anterior chamber, and the IOP to acceptable levels in NVG patients [8-12]. Fluorescein angiography and histochemical investigations demonstrated that there was less vascular permeability and inflammatory reaction in trabecular tissue with IVB than without IVB [13,14]. Another histopathological investigation indicated that IVB may induce changes in immature, newly formed vessels, leading to endothelial apoptosis with vascular regression and inducing the normalization of premature vessels in PDR or NVG eyes [15].…”
Section: Introductionmentioning
confidence: 99%
“…In our group, no statistically significant difference was found in the average iris thickness between PRP-treated eyes and nontreated eyes and also between anti-VEGF treated eyes and nontreated eyes. The anti-VEGF injection strongly inhibits vascular permeability [ 14 ] and promotes regression of immature vessels while inducing normalization and maturation of premature vessels [ 15 ]. Further studies should clarify the effect of PRP and the anti-VEGF injection on iris thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshida et al 25 demonstrated reduced vascular permeability, decreased inflammatory reaction, loss of vascular function and endothelial cell degeneration in trabecular tissues of patients undergoing trabeculectomy for NVG.…”
Section: Conceptmentioning
confidence: 99%